PENGARUH BAURAN PEMASARAN TERHADAP MINAT KUNJUNGAN WISATAWAN PADA OBYEK WISATA ALAM MALINO DI KABUPATEN GOWA - Asdi, Asdi (Jurnal Ilmiah Pena: Sains dan Ilmu Pendidikan, 2018)
This study aimed to determine whether the marketing mix was significantly against the interest of tourists visiting natural attractions Malino Gowa. The experiment was conducted on the natural attractions Malino Village MalinoTinggimoncongGowa district. The amount of sample determined by using a formula that is as much as 100 Slovin tourists. The sample for the study using random sampling techniques, while the data collection techniques kuissioner. Processing and analysis of data using analytical techniques contingency coefficient, phi coefficient, coefficient of determination, and significance test t test at 95% significance level. The results of data analysis showed that the value; contingency coefficient of 0.617, phi coefficient of 0.784, and a coefficient of determination of 61.5%. While the significance test t test obtained at 12.518 t count is greater than t table by 1.980. Based on the coefficient values above show that the marketing mix variable was significantly by 61.5% to variable interest tourists visit the natural attractions Malino Gowa, while the rest of 38.5% is influenced by other variables that are not investigated in this study.Â Keywords: marketing mix, interest tourists.